2013
DOI: 10.3906/sag-1202-80
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, clinical features, and laboratory detection of Mycoplasma pneumoniae infection in East Azerbaijan, Iran

Abstract: Examining and measuring levels of suspended sediments of water column is a common application of close range remote sensing, because the technology offers an efficient and economical means of studying water quality problems. The aim of this experiment was to use close range remote sensing to determine the effect of increasing suspended sediment concentration containing different levels of organic matter on algal spectral patterns. The experiment was conducted in a small room with a 65-l volume water container.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…18 Also, the study of Ghotaslou et al carried out on 51 patients with lower respiratory tract infection in Azerbaijan revealed that about 6.15% of them had M. pneumoniae. 17 Similar frequencies of this pathogen have been reported in other studies from other parts of the world, like those of Elkholy et al and Meijer et al involving 111 Egyptian children and 557 Dutch patients with the positivity rates of only 4.5% 19 and 1.3%, 20 respectively. However, a relatively high frequency of the infection (>19%) has been reported in our neighboring countries, such as Turkey.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…18 Also, the study of Ghotaslou et al carried out on 51 patients with lower respiratory tract infection in Azerbaijan revealed that about 6.15% of them had M. pneumoniae. 17 Similar frequencies of this pathogen have been reported in other studies from other parts of the world, like those of Elkholy et al and Meijer et al involving 111 Egyptian children and 557 Dutch patients with the positivity rates of only 4.5% 19 and 1.3%, 20 respectively. However, a relatively high frequency of the infection (>19%) has been reported in our neighboring countries, such as Turkey.…”
Section: Discussionsupporting
confidence: 82%
“…16 Even though we recorded a high frequency (26.4%) of M. pneumoniae in our study, low frequencies (1-6.15%) have been reported in several studies in Iran. 17,18 The research conducted by Oskooee et al involving 102 CAP patients displayed the positivity rate of only 1% for M. pneumoniae. 18 Also, the study of Ghotaslou et al carried out on 51 patients with lower respiratory tract infection in Azerbaijan revealed that about 6.15% of them had M. pneumoniae.…”
Section: Discussionmentioning
confidence: 98%
“…The frequency of these microorganisms using culture in other regions including 10.33% in Japan (20), 2.01% in Iran (21), and 10.8% in Serbia (22) was different in comparison with that of the current study. There are some controversies about the gold standard method to diagnose M. pneumoniae.…”
Section: Discussionmentioning
confidence: 40%
“…Overall, 53% of patients had elevated IgG level and only 5.3% had IgM positive test results, which indicated active M. pneumoniae infection (19). In a study in Greek, 225 children, who were hospitalized for respiratory tract infections were assessed regarding the presence of IgG and IgM antibodies by ELISA (20).…”
Section: Discussionmentioning
confidence: 99%